The Influence of the Implementation of the Merdeka Curriculum on the Religious Development of Students in Makassar City Middle Schools - Sandi Pratama (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
The implementation of the Independent Curriculum in junior high schools (SMP) in Makassar City aims not only to improve student academic achievement but also to strengthen moral and spiritual values. Religious guidance is a crucial aspect of this curriculum, which is expected to shape students' character and noble morals. This study was conducted to determine the influence of the Independent Curriculum on the religious guidance patterns of junior high school students in Makassar City. This research used a survey method with a quantitative approach. The quantitative approach aims to test specific theories by examining the relationships between the variables studied. These variables are measured using research instruments, resulting in numerical data that can then be analyzed using statistical procedures. The sample in this study consisted of 30 junior high school teachers in Makassar City who were randomly selected using a random sampling method. Data collection was carried out by distributing questionnaires to respondents and conducting documentation. The results showed that the significance value obtained was 0.002, which is smaller than the alpha of 0.05. This indicates that there is a significant influence between the Independent Curriculum (X) and religious guidance (Y) of students in Makassar City Junior High Schools. This test is strengthened by the F count result of 11.56, while the F table value for n: 30 is 2.27. Because the F count value is greater than the F table (11.56 > 2.27), it can be concluded that the Independent Curriculum has a significant influence on students' religious guidance.